Implementation Of The Deming Cycle In The School Quality Assurance System - Trisnantari, Hikmah Eva; Jannah, Siti Raudatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyse the implementation of the Plan-Do-Check-Act (PDCA) model within the quality assurance system at SMK Sore Tulungagung. Previous studies emphasise that PDCA is essential for institutional quality improvement, yet its application in vocational schools remains underexplored. In Indonesia, ISO-based management systems have encouraged schools to adopt structured planning and evaluation mechanisms. This research uses a qualitative case study design through in-depth interviews, observations, and documentation. Key informants include the principal, the internal quality assurance team, and the administrative staff. The findings show that the planning stage involves comprehensive program mapping aligned with ISO 9001:2015 and risk management principles. The implementation stage demonstrates clear documentation, defined responsibilities, and responsive service flows. The evaluation stage incorporates satisfaction surveys, internal audits, and management review meetings that ensure issues are systematically addressed. Follow-up actions are carried out through corrective measures and continuous improvement efforts. The study also finds that digital monitoring is still limited, affecting long-term consistency. Overall, the PDCA model strengthens the school’s quality culture and operational effectiveness. This study demonstrates how an adaptive, data-driven PDCA framework can enhance internal quality assurance in vocational institutions and recommends integrating digital monitoring systems to ensure sustainability.